Langkah-Langkah Organisasi Untirta Movement Community (Umc) Dalam Memperkuat Nilai Demokrasi Di Kalangan MahasiswaLangkah-Langkah Organisasi Untirta Movement Community (Umc) Dalam Memperkuat Nilai Demokrasi Di Kalangan Mahasiswa - Sunggu, Oktavia Theresia Ompu; Fitrayadi, Dinar Sugiana; Untari, Aryanti Dwi (UNTIRTA CIVIC EDUCATION JOURNAL, 2024)
The value of democracy among students plays an important role in creating a critical and progressive academic environment. Untirta Movement Community (UMC) as an external organization at Sultan Ageng Tirtayasa University strives to strengthen democratic values through various advocacy activities and concrete actions. This study aims to analyze the steps taken by UMC in strengthening the democratic values of students. The research method used is a qualitative approach with techniques such as interviews, observations, and documentation. The research results show that UMC implements various strategies, such as public discussions, grand deliberations, cadre training based on liberation theology, and demonstration actions involving various elements of society. These measures are effective in enhancing students' understanding of democratic values, including tolerance, freedom of expression, and awareness of differences. However, challenges such as low student participation and the potential for conflict in actions remain a concern. In conclusion, UMC serves as an important platform for students to understand and actively implement democratic principles within the campus and society.